From perceptions by beneficiaries, can homelessness be reduced through self-help housing in the central region of South Africa? - Qumbisa, Nolwazi; Emuze, Fidelis; Smallwood, John (Frontiers in Sustainable Cities, 2025)
As an alternative housing approach, self-help housing has been implemented for many years, particularly in developing nations. This study aimed to evaluate the potential of self-help housing as a mitigation strategy for reducing homelessness in South Africa. The focus was on the perception that housing is commonly regarded as a fundamental necessity the government provides, even though beneficiaries ultimately construct their own homes. A qualitative study was conducted using semi-structured interviews with 25 key informants involved in five projects located in the central region of South Africa. The objective was to assess the effectiveness of self-help housing in addressing homelessness, understand beneficiary perceptions, and identify the challenges associated with conventional and non-conventional housing delivery methods. The key findings revealed that while both methods present challenges, beneficiaries preferred self-help housing due to their involvement in the projects, the larger housing units they received, and their overall satisfaction with the outcomes. The study concluded that there is a need to reform self-help housing policies in South Africa to efficiently regulate and support incremental housing initiatives across the country.